THE EFFECT OF “SPEAK uP” TRAINING TOWARD APPREHENSION OF SPEAKING IN FRONT OF PUBLIC - Rizky Nur Amalia; Farida Hidayati (Jurnal EMPATI, 2013)
This study is aimed to evaluate the effect of “SPEAK uP” training toward apprehension of speaking in front of public.The characteristic subject of this study is to students of SMK Negeri 8 Semarang who took social worker studies as their major; mostly they are having apprehension in ability of speaking in front of public with high and extra high category level on apprehension of speaking in front of public, those students had agreed to join “SPEAK uP” training completely. This study generally used experimental method that consists of non randomized pretest-posttest with control group design. This study was conducted to over 40 students that separated in two groups in which first group contain of  20 students as experimental group and the second one contain of 20 students too as control group. The treatment was given to experiment group by using “SPEAK uP” training and held in three times. Data collection process was acted by using the scale of apprehension in speaking in front of public consisting of three components: the physical component, the component of emotion and cognitive component.The result of hypothesis test with Independent Sample T-Test and Paired Sample T-Test produced score te > tt (2,101) with p < 0,05. In general, “SPEAK uP” shown that there were significant effect after “SPEAK uP” training toward apprehension in speaking in front of public.